PENGEMBANGAN MEDIA PEMBELAJARAN HOLOGRAM 3D BERBASIS ANDROID PADA PEMBELAJARAN IPA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 5 SDN WONOSARI 01 KOTA SEMARANG - Ridho, Faisal Miftakhul; Tyas, Dewi Nilam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The use of conventional learning media, such as textbooks for science subjects, reduces students' motivation to participate in lessons. There must be innovation in learning activities, one of which is by using technology such as 3D hologram animation. This research examines the development, testing the feasibility and effectiveness of android-based 3D hologram learning media for 5th grade science learning material on human eye organs. The method used is R&D or development research with the ADDIE research model which has several steps in its research including; analysis (analyze), design (design), development (development), implementation (implementation), and evaluation (evaluation). The results obtained from this study include an assessment of the validation of media experts with a percentage score of 95%, which means that the developed media receives a category that is very feasible to be tested in the science learning process at school. Then the results of media trials using a large scale with a total research population of 23 students conducted in grade 5 SDN Wonosari 01 Semarang City showed an increase in student learning outcomes after the use of hologram learning media. The data on the increase in learning outcomes is supported and evidenced by the results of the N Gain test which obtained an N Gain score with a percentage of 73.89% with an interpretation that it is effective enough to improve the learning outcomes of grade 5 students in science subjects at SDN Wonosari 01 Semarang City.